Evaluation of the anti-inflammatory, antioxidant, and cytotoxic potential of Cardamine amara L. (Brassicaceae): A comprehensive biochemical, toxicological, and in silico computational study - Basit, Abdul; Ahmad, Saeed; Khan, Kashif ur Rehman; Aati, Hanan Y.; Sherif, Asmaa E.; Ovatlarnporn, Chitchamai; Khan, Safiullah; Rao, Huma; Arshad, Muhammad Adeel; Shahzad, Muhammad Nadeem; Perveen, Shagufta (Frontiers in Chemistry, 2023)
Cardamine amara L. (Brassicaceae) is an important edible plant with ethnomedicinal significance. This study aimed at evaluating the phytochemical composition, anti-inflammatory, antioxidant and cytotoxicity aspects of the hydro-alcoholic extract of C. amara (HAECA). The phytochemical composition was evaluated through total phenolic contents (TPC), total flavonoid contents (TFC) determination and UPLC-QTOF-MS profiling. Anti-inflammatory evaluation of HAECA was carried out through the carrageenan induced paw edema model. Four in vitro methods were applied in the antioxidant evaluation of HAECA. MTT assay was used to investigate the toxicity profile of the species against human normal liver cells (HL7702), human liver cancer cell lines (HepG2) and human breast cancer cell lines (MCF-O7). Three major compounds (Gentisic acid, skullcapflavone and conidendrine) identified in UPLC-Q-TOF-MS analysis were selected for in silico study against cyclooxygenase (COX-I and COX-II). The findings revealed that HAECA is rich in TPC (39.32 ± 2.3 mg GAE/g DE) and TFC (17.26 ± 0.8 mg RE/g DE). A total of 21 secondary metabolites were tentatively identified in UPLC-Q-TOF-MS analysis. In the MTT cytotoxicity assay, the extract showed low toxicity against normal cell lines, while significant anticancer activity was observed against human liver and breast cancer cells. The carrageenan induced inflammation was inhibited by HAECA in a dose dependent manner and showed a marked alleviation in the levels of oxidative stress (catalase, SOD, GSH) and inflammatory markers (TNF-α, IL-1β). Similarly, HAECA showed maximum antioxidant activity through the Cupric reducing power antioxidant capacity (CUPRAC) assay (31.21 ± 0.3 mg TE/g DE). The in silico study revealed a significant molecular docking score of the three studied compounds against COX-I and COX-I. Conclusively the current study encourages the use of C. amara as a novel polyphenolic rich source with anti-inflammatory and antioxidant potential and warrants further investigations on its toxicity profile.